2022
DOI: 10.21833/ijaas.2022.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of factors affecting the business efficiency of seafood companies listed on the stock market of Vietnam

Abstract: This study aims to examine the factors affecting the business efficiency of companies in the seafood industry listed on the Vietnamese stock market. The article analyzes the data collected from the financial statements of 20 listed seafood companies operating in Vietnam from 2016 to 2020. The study uses EViews software in quantitative analysis to build a panel data regression model to determine the relationship and level of impact of internal factors on the business performance of seafood companies. Business e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…As mentioned by Pham and Thu Ho (2022), another opportunity for innovation in sustainability reporting is the incorporation of zakat, an Islamic form of almsgiving, into digital accounting systems. A novel method of CSR and sustainability reporting is the incorporation of zakat into financial systems, especially for businesses operating in areas where zakat is a common practice (Al- Malkawi and Javaid, 2018).…”
Section: Innovations In Sustainability Reportingmentioning
confidence: 99%
“…As mentioned by Pham and Thu Ho (2022), another opportunity for innovation in sustainability reporting is the incorporation of zakat, an Islamic form of almsgiving, into digital accounting systems. A novel method of CSR and sustainability reporting is the incorporation of zakat into financial systems, especially for businesses operating in areas where zakat is a common practice (Al- Malkawi and Javaid, 2018).…”
Section: Innovations In Sustainability Reportingmentioning
confidence: 99%
“…Studies by researchers such as Abor (2005), Zeitun and Tian (2007), Onaolapo and Kajola (2010), Ahmad et al (2012), Abdullah and Tursoy (2021), Pham and Thu Ho (2022), and Cuc et al (2023) have shown that a larger company size positively affects its performance. Zeitun and Tian (2007) and Abor (2005) suggested that companies with high growth potential tend to perform better because they can generate good returns on investment.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined the factors influencing the P/E ratio with a focus on developed countries and using various financial proxies for earnings growth, dividend payout, risk, and discount rates (Rahman & Shamsuddin, 2019;Sajeetha et al, 2023), however the research results are not consistent. Moreover, there is a lack of research on the influencing factors of the P/E ratio in developing countries (Freihat, 2019) like the Vietnamese context, especially in-depth investigations of steel companies listed on the stock exchanges (Ho et al, 2023). Different from economic factors such as GDP growth rate or inflation rate where the value of these indexes has a macroeconomic impact and is influenced by many factors in different fields, financial variables brings a more significant result and direct view and when it is associated with the real performance of steel enterprises.…”
Section: Introductionmentioning
confidence: 99%